On the approximation of the function on the unite sphere by the spherical harmonics - Rakhimov, Abdumalik (2022)
It is considered the problems of the approximation of the functions defined on the surface of the unite ball in N dimensional spaces by the harmonic polynomials orthogonal on the surface.